Current Topics in Neglected Tropical Diseases - Rodriguez-Morales, Alfonso J. (Infectious Diseases, 2019)
Neglected tropical diseases (NTDs) is a diverse group of communicable diseases that prevail in tropical and subtropical conditions in 149 countries. NTDs affect more than one billion people and cost developing economies billions of dollars every year. According to the World Health Organization (WHO), NTDs mainly affect populations living in poverty, without adequate sanitation, and in close contact with infectious vectors, domestic animals, and livestock. Migration, as well as climate change and variability, are key factors in NTD prevalence. Therefore, NTDs deserve more study. Recently, viruses transmitted by vectors (arboviruses) that affect not only people living in the tropics, but also travelers and migrating populations, have been causing epidemics. Examples of these viruses include Dengue, Chikungunya, Zika, Mayaro, and encephalitis viruses. These viruses emerge and reemerge in multiple regions of the world, as occurred in the Americas recently (2013-2017) with Chikungunya and Zika. This book aims to update the significant epidemiological and clinical research of NTDs in many aspects with a multinational perspective.